Prediction of Concrete Shrinkage Occurring Prior to External Loading and Effect on Short-Term Constitutive Modeling and Design. Issue 6 (June 2013) - Gribniak, Viktor; Torres, Lluis; Kaklauskas, Gintaris; Daniunas, Alfonsas; Kacianauskas, Rimantas; Jakubovskis, Ronaldas
Although shrinkage effect is traditionally taken into account in the assessment of long-term deformation of concrete structures, it may significantly affect cracking resistance and deformations of reinforced concrete members subjected to short-term load. Though generally neglected, the shrinkage effect may be of high significance in constitutive modeling of tension-stiffening, particularly, when it is based on tests of reinforced concrete members. Disregarding the shrinkage effect may result in considerable errors of deflection predictions. This paper statistically investigates the accuracy of several well-known free shrinkage strain prediction techniques: Eurocode 2, ACI 209, CNIIS (Russia), Bažant & Baweja's (B3), and Gardner & Lockman's (GL 2000). Accuracy of shrinkage prediction models and the influence of shrinkage assessment errors on constitutive modeling and deformation prediction results are illustrated and discussed. Unlike the previous investigations, the present study considers a shrinking period characteristic to the age of a member at first loading. The manuscript reports recommendations useful for short-term constitutive and deformation analysis of reinforced concrete.